The Relationship between Sodium Intake and Nutritional Status with Hypertension Incidence in the Work Area of the Alosika Health Center, Konawe Regency - Islawati Islawati; Ellyani Abadi; Desiderius Bela Dhesa (LPPM STIKes Karya Kesehatan, 2023)
Abstract. Hypertension is a condition where blood pressure exceeds 140/90 mmHg. Hypertension can cause complications of cardiovascular diseases such as stroke, heart disease and diabetes mellitus. Hypertension at the Alosia Health Center in 2021 was 72 cases and increased in 2022 for the January-March period by 90 cases. The purpose of this study was to determine the relationship between sodium intake and nutritional status with the incidence of hypertension. Quantitative research design, cross sectional study approach. The sample is partly all patients registered at the Alosika Health Center, Konawe Regency in 2022 for the January-March 2022 period as many as 89 obtained by Simple Random Sampling. Data were analyzed using Chi-square test. The results of the study from 89 samples, the incidence of hypertension, most of them had hypertension (66.3%), then based on sodium intake, most were more (67.4%) and based on nutritional status most of 56 people (62.9%) nutritional status normal. Chi-Square test obtained p value 0.000 for the relationship of sodium intake with the incidence of hypertension and p value 0.001 for the relationship between nutritional status and the incidence of hypertension. The conclusion of this study is that there is a relationship between sodium intake and nutritional status with the incidence of hypertension in the work area of the Alosika Health Center, Konawe Regency.